2016
DOI: 10.5173/ceju.2016.883
|View full text |Cite
|
Sign up to set email alerts
|

Role of cigarette smoking in urological malignancies and clinical interventions for smoking cessation

Abstract: IntroductionCigarette smoking is the single greatest preventable cause of disease and death. Our literature review highlights the increased risk of cigarette smoking and kidney cancer, bladder cancer and prostate cancer.Material and methodsSmoking cessation improves outcomes at all stages of these disease processes, where patients who quit for 10–20 years appear to obtain a similar risk as those who have never smoked, even after diagnosis of disease.ResultsUrologists, however, very seldom provide smoking cessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Cigarette smoking is considered one of the greatest risk factors in the development of cardiovascular disease and is a potent metabolic stimulator in the progression of various types of cancer, including prostate cancer (1). Studies indicate that secondhand or sidestream smoke contains higher concentrations of toxic components than mainstream smoke, and secondhand smoke exposure is a factor in the development of smoking-related diseases (2).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is considered one of the greatest risk factors in the development of cardiovascular disease and is a potent metabolic stimulator in the progression of various types of cancer, including prostate cancer (1). Studies indicate that secondhand or sidestream smoke contains higher concentrations of toxic components than mainstream smoke, and secondhand smoke exposure is a factor in the development of smoking-related diseases (2).…”
Section: Introductionmentioning
confidence: 99%
“…Current smoking at the time of UCB diagnosis is associated with an additional 24% increase in the recurrence risk compared to a history of smoking in the past. Urological advice and assistance in quitting smoking are suboptimal, despite the fact of their relevance and efficacy (Sosnowski et al 2016 ). A prospective trial showed that a short 5 min brief smoking cessation intervention increased the rate of UBC patients who quit smoking (12.1 vs 2.6%) compared to patients under usual care (Bjurlin et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…6 Quitting after a diagnosis can improve cancer, quality-of-life, and all-cause mortality outcomes. [7][8][9][10][11] Improving how and how often urologists help patients to quit tobacco will improve patient health outcomes. 12 Tobacco use screening and treatment with combination behavioral counseling and pharmacotherapy are evidencebased practices (EBPs).…”
Section: Introductionmentioning
confidence: 99%